Inflammasomes in the gastrointestinal tract: infection, cancer and gut microbiota homeostasis - Man, Si Ming (Nat Rev Gastroenterol Hepatol, 2018)
Inflammasome signalling is an emerging pillar of innate immunity and has a central role in the regulation of gastrointestinal health and disease. Activation of the inflammasome complex mediates both the release of the pro-inflammatory cytokines IL-1β and IL-18 and the execution of a form of inflammatory cell death known as pyroptosis. In most cases, these mediators of inflammation provide protection against bacterial, viral and protozoal infections. However, unchecked inflammasome activities perpetuate chronic inflammation, which underpins the molecular and pathophysiological basis of gastritis, IBD, upper and lower gastrointestinal cancer, nonalcoholic fatty liver disease and obesity. Studies have also highlighted an inflammasome signature in the maintenance of gut microbiota and gut–brain homeostasis. Harnessing the immunomodulatory properties of the inflammasome could transform clinical practice in the treatment of acute and chronic gastrointestinal and extragastrointestinal diseases. This Review presents an overview of inflammasome biology in gastrointestinal health and disease and describes the value of experimental and pharmacological intervention in the treatment of inflammasome-associated clinical manifestations.